2019
DOI: 10.3389/fphar.2019.01217
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Analysis of circRNA-miRNA-mRNA Molecular Regulatory Networks During Herba Gelsemium elegans Intoxication

Abstract: Gelsemium elegans (Gardner & Champ.) Benth. (GE) has therapeutic effects for pain and malignant tumors but also has high toxicity. Its mechanism of toxicity has not yet been fully clarified, thus limiting its application. Meanwhile, evidence has shown that circRNAs are closely related to the progression of disease. However, very little is known about their expression profiles during intoxication. In this paper, circRNA/mRNA microarrays were respectively performed to detect their expression profiles in mice wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…51 It is well established that circRNAs/miRNA/ mRNA axes may serve as molecular regulatory networks during gene expression, and aberrant expression of any of the molecules involved in these axes may promote disease progression, including glioma development. 52,53 Thus, it is essential to unravel the regulatory network of noncoding RNAs and coding genes in the process of tumor pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…51 It is well established that circRNAs/miRNA/ mRNA axes may serve as molecular regulatory networks during gene expression, and aberrant expression of any of the molecules involved in these axes may promote disease progression, including glioma development. 52,53 Thus, it is essential to unravel the regulatory network of noncoding RNAs and coding genes in the process of tumor pathology.…”
Section: Discussionmentioning
confidence: 99%
“…ciRS‐7 acts as a sponge of miR‐7 and regulates EGFR/RAF1 pathways in colorectal cancer, 50 and circ‐ITCH is involved in esophageal squamous cell carcinoma by interacting with miR‐7, miR‐17, and miR‐124 51 . It is well established that circRNAs/miRNA/mRNA axes may serve as molecular regulatory networks during gene expression, and aberrant expression of any of the molecules involved in these axes may promote disease progression, including glioma development 52,53 …”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with a study on human circRNAs 29 . In addition, we found that circRNAs in SPEVs were distributed on all chromosomes, and the number of circRNAs was the highest on chromosome 1 39 . Interestingly, we found 125 circRNAs that were derived from mitochondria for the first time, and these circRNAs may play an important role in sperm motility.…”
Section: Discussionmentioning
confidence: 82%